La sobreprotección de marcas notoriamente conocidas: análisis crítico del caso McDonald’s vs McHotel Ica - García Enríquez, Jonathan Rafael; Cachay Vásquez, Emyly Yelin (Pontificia Universidad Católica del Perú, 2025)
This article analyzes the legal foundation of the Indecopi's decisions in the case of McDonald’s vs. McHotel Ica, evaluating its impact on the protection of well-known trademarks and competition in the Peruvian market. A qualitative approach is used to examine the arguments of both parties and the justifications for the decisions in the first and second instances. Resolutions from Indecopi, cases from the Andean Tribunal, and relevant regulations such as Decision 486 of the Andean Community and Legislative Decree 1075 are reviewed. The conclusion highlights that the protection of well-known trademarks must be balanced to avoid overprotection that limits competition. The McDonald’s vs. McHotel Ica case underscores the importance of establishing limits on trademark protection and the need for consistent criteria in Indecopi's decisions to promote a fair competitive environment.

Este artículo analiza la fundamentación jurídica de las decisiones del Indecopi en el caso McDonald’s vs McHotel Ica, evaluando su impacto en la protección de marcas notoriamente conocidas y la competencia en el mercado peruano. Se utiliza un enfoque cualitativo para examinar los argumentos de ambas partes y las justificaciones de las decisiones en primera y segunda instancia. Se revisan resoluciones del Indecopi, casos del Tribunal Andino y normativa relevante, como la Decisión 486 de la Comunidad Andina y el Decreto Legislativo 1075. La conclusión destaca que la protección de marcas notoriamente conocidas debe equilibrarse para evitar la sobreprotección que limite la competencia. El caso McDonald’s vs McHotel Ica subraya la importancia de establecer límites en la protección de marcas y la necesidad de criterios consistentes en las decisiones del Indecopi para fomentar un entorno competitivo equitativo.
The overprotection of well-known trademarks: a critical analysis of the McDonald’s vs McHotel Ica case
Keywords: Trademarks; Well-known trademarks; Opposition; Overprotection; Indecopi; Marcas; Marcas notoriamente conocidas; Oposición; Sobreprotección; Indecopi; https://purl.org/pe-repo/ocde/ford#5.05.00